2023
DOI: 10.1002/slct.202204191
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylate‐ and Sulfonate‐Containing Quinazolin‐4(3H)‐one Rings: Synthesis, Characterization, and Carbonic Anhydrase I–II and Acetylcholinesterase Inhibition Properties

Abstract: Quinazolines are a group of bioactive heterocyclic compounds with a wide range of biological activities and have gained an important place in the design of active drugs with various targets due to their pharmacological properties. Carbonic anhydrase (CA) and acetylcholinesterase (AChE) inhibitors are very important pharmacologically. In this study, inhibition effects of newly synthesized quinazolin‐4(3H)‐one derivatives on human erythrocyte CA‐I (hCA‐I) and CA‐II (hCA‐II) isoenzyme and AChE activity were inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…Therefore, finding and creating both a preventive and a curative treatment for AD is the researchers' ultimate goal. [32] The inhibitory effects of the novel compounds (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) on AChE are shown in Table 2. The AChE inhibition profiles of the compounds evaluated here were quite interesting.…”
Section: Bioactivity Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, finding and creating both a preventive and a curative treatment for AD is the researchers' ultimate goal. [32] The inhibitory effects of the novel compounds (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) on AChE are shown in Table 2. The AChE inhibition profiles of the compounds evaluated here were quite interesting.…”
Section: Bioactivity Resultsmentioning
confidence: 99%
“…CA inhibitors are the therapeutic agents used to control the hyper activity of CA. CAI have been prescribed and administered for the treatment of glaucoma, diuresis, epilepsy, osteoporosis, and gastric ulcer [9,10] . In the central and peripheral nervous systems of vertebrates and invertebrates, cholinesterases hydrolyze the neurotransmitter acetylcholine.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study by Tokalı et al ., inhibition properties of the new quinazolin‐4(3 H )‐one analogues against hCA I–II were evaluated in vitro and in silico . They reported that the new compounds showed inhibition at the nanomolar level and that compound 4‐[(4‐Oxo‐2‐(phenoxymethyl)quinazolin‐3(4 H )‐ylimino)methyl]phenyl furan‐2‐carboxylate (IC 50 : 205 nM) was the most potent compounds in the series for hCA I and compound 4‐[(4‐oxo‐2‐(phenoxymethyl)quinazolin‐3(4 H )‐ylimino)methyl]phenyl isobutyrate (IC 50 : 209) nM for hCA II [31] . When the results of this study are compared with our study, it is seen that our compounds have lower IC 50 values.…”
Section: Resultsmentioning
confidence: 99%